PENCIPTAAN BUSANA CASUAL READY TO WEAR DENGAN SUMBER IDE KLONO SEWANDONO DAN BUJANG GANONG PADA SENI REOG PONOROGO - Daniswari Syandani, Tsabina; Nahari, Inty; Mayasari, Peppy; Tri Rahayu, Imami Arum (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
This research is a study on the creation of casual ready-to-wear clothing that interprets the characters of Klono Sewandono and Bujang Ganong in the art of Reog Ponorogo. Klono Sewandono depicts a brave, authoritative, and wise king. Bujang Ganong depicts an energetic, agile, and unyielding prime minister. The research method used in this study is Practice-led Research, which includes the pre-design, design, implementation, and presentation stages. The purpose of this research is to describe the creative process of creation, the final results of the creation process, and the presentation of the creation of casual ready-to-wear clothing inspired by Klono Sewandono and Bujang Ganong. The benefits of this research are as a form of applying knowledge in the creation of casual ready-to-wear clothing inspired by Klono Sewandono and Bujang Ganong in the art of Reog Ponorogo, as well as an effort to preserve local culture, particularly in the Ponorogo region. The final products of this research comprise two women's garments and one men's garment, with visual inspiration drawn from the colours, silhouettes, and costume elements of each character. The garments created were exhibited at the Grand Jury event, a fashion exhibition and show.